Pengaruh Free Cash Flow dan Financial Leverage Terhadap Earning Management dengan Good Corporate Governance sebagai Variabel Moderasi - Kosasih, Tjindrawati; Paramitha, Melvie (Jurnal Syntax Fusion, 2021)
Earning Management is one of the various efforts that can be made by companies in engineering the numbers in the financial statements so that the company's financial statements can be seen in good condition for investors and other readers. This study aims to determine the effect of free cash flow and financial leverage on earnings management with good corporate governance as a moderating variable in transportation service companies. This study uses data from 26 transportation service companies from 2017-2019 that have been listed on the Indonesia Stock Exchange. The data analysis technique used in this study is the Partial Least Square (PLS) analysis method where PLS analysis is an analytical method that is not based on many assumptions or conditions and can handle many variables at once even though there is multicollinearity in these variables. The results show that free cash flow and financial leverage have no effect on earning management and good corporate governance cannot moderate the relationship between free cash flow and financial leverage on earning management.